2020
DOI: 10.1364/boe.395683
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning improves contrast in low-fluence photoacoustic imaging

Abstract: Low fluence illumination sources can facilitate clinical transition of photoacoustic imaging because they are rugged, portable, affordable, and safe. However, these sources also decrease image quality due to their low fluence. Here, we propose a denoising method using a multi-level wavelet-convolutional neural network to map low fluence illumination source images to its corresponding high fluence excitation map. Quantitative and qualitative results show a significant potential to remove the background noise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 53 publications
0
64
0
Order By: Relevance
“…Regardless of the source, the strong signal from skin can make detecting follicles under the skin surface challenging. Thus, we used a skin tracing technique (digital image processing) to remove signal from the skin surface to facilitate improved image formation [ 42 , 43 ]. Figure 4 D shows the skin trace from Figure 4 C. We removed the photoacoustic contribution from the skin surface to obtain Figure 4 E. Figure 4 F,G show the shaved stomach imaged at 690 and 850 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the source, the strong signal from skin can make detecting follicles under the skin surface challenging. Thus, we used a skin tracing technique (digital image processing) to remove signal from the skin surface to facilitate improved image formation [ 42 , 43 ]. Figure 4 D shows the skin trace from Figure 4 C. We removed the photoacoustic contribution from the skin surface to obtain Figure 4 E. Figure 4 F,G show the shaved stomach imaged at 690 and 850 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, their output energy is low, typically in the range of nJ/pulse to . 118 The low energy leads to low signal intensity and thus reduced image quality. A favorable property of PLD/LED is that they have high repetition frequency, typically on the order of kHz and above.…”
Section: Applications Of DL In Paimentioning
confidence: 99%
“…used a modified U-Net, termed multi-level wavelet-CNN, in which the pooling operations were replaced by discrete wavelet transform (DWT), and pooling operations were replaced by DWT, and the upsampling operations were replaced by inverse wavelet transform, to enhance PA image quality in a low SNR setting. 118 They used the PA images taken at a fluence of as the ground truth and then reduced the laser fluence down to 0.95 and to train the network. In in vivo experiment, mice injected with various concentrations of methylene blue (MB) were imaged, and the CNR improvement factor was 1.55, 1.76, 1.62, and 1.48 for a dye concentration of 0.05, 0.1, 1.0, and 5.0 mM, respectively.…”
Section: Applications Of DL In Paimentioning
confidence: 99%
“…In an extensive study, the U-Net-based postprocessing approach was successfully applied to in vivo measurements 105 and showed clear improvements over backprojection-based algorithms when the data were undersampled or detected over a partial aperture (limited-view problem). Hariri et al 106 showed that this approach can improve in vivo imaging when using low-fluence sources. The observation of improved visual performance for in vivo applications was also reported in other studies.…”
Section: Application To In Vivo Imagingmentioning
confidence: 99%